The Obama Presidency : Promise and Performance. - Crotty, William (Lexington Books, 2012)
A comprehensive analysis of the Obama presidency, its actions in office and its policy directions. The changes in orientation and policy directions that took place are both accounted for and explained in a policy and political context as are their consequences for the institution of the presidency itself.